Should We Teach English to Our Kids in Indonesia? - Ibnu Herlambang; Athaya Hanifah Adri (PAEDAGOGIA, 2024)
The influence of the English language in a globalized world has been acknowledged internationally. This widespread use underscores the importance of imparting English skills to individuals from a young age. However, recent changes in the Indonesian curriculum reflect ongoing debate, as primary school students are no longer mandated to learn English. This leads to the inquiry “Is English not that important for children?” and “Should we teach English to young learners?”. The study delves into the discourse on teaching English to young learners in Indonesia, aiming to understand English teachers’ perspectives on this matter. Two experienced English teachers who specialize in instructing young learners in Indonesia were engaged using interviews. Employing the narrative inquiry technique, the study seeks a comprehensive exploration of their educational experiences (Baden & Niekerk, 2007). The study's findings reveal a consensus among the teachers that teaching English to young learners in Indonesia has more advantages than drawbacks. Both educators argue that early exposure to the language enhances children's confidence and vocabulary knowledge, fostering a solid foundation for their future endeavors. This insight challenges the recent curriculum change and prompts a reevaluation of the decision to exclude English from the mandatory syllabus for young students. In conclusion, the study advocates for reconsidering the current educational approach in Indonesia, emphasizing the benefits of introducing English to young learners. It highlights the positive impact on children's linguistic development and overall educational trajectory, suggesting that early English education contributes significantly to their long-term success